(untitled) (Journal of the Bangladesh Chemical Society, 2013)
Organic field effect transistors with an active layer based on the tetracene single-crystal were fabricated. It was found that organosilane self-assemble monolayer (SAM) modified device with tetracene single-crystals gave higher mobility and on/off ratio rather than untreated device. SAM modified tetracene single-crystal transistors with parylene gate insulator showed the highest mobility of 0.66 cm2 V-1 s-1 and high on/off ratio of 104. This finding demonstrates that SAM treatment decrease the charge leakage between source and drain which help to decrease the off current with greater extent and increase the on current slightly of the tetracene single-crystal field-effect transistors. Journal of Bangladesh Chemical Society, Vol. 25(2), 194-199, 2012 DOI: http://dx.doi.org/10.3329/jbcs.v25i2.15086